Pengaruh profitability, liquidity, leverage, dan interest rates terhadap stock return untuk LQ-45 Index - Soni Firmansyah; Linda Purnamasari (STIE Perbanas Surabaya, 2017)
The purpose of investors to invest their fund is to get the stock return. Therefore, they need to understand the company's financial performance and macro-economic factors that can affect the acquisition of stock returns. This study tried to analyze the effects of profitability, liquidity, leverage, and interest rates on stock return. The data were taken from the stock in LQ-45 index period 2012-2014. The sample was taken using a purposive sampling obtained a sample of 24 companies. Analysis techniques used multiple linier regression analysis, the result shows simultaneously return on equity, quick ratio, debt to equity ratio, and interest rates have significant effect on stock return. Partially return on equity and quick ratio have no significant effect on stock return and debt to equity ratio and interest rate have significant effect on stock return.